Pharmacists and Pharmacy Technicians in Clinical Settings: A Team-Based Approach to Reducing Medication Errors and Enhancing Patient Support - Hisham Ahmed Ali Al-Zahrani; Abdulmajeed Abdullah Hamed; Mohammed Junaydib Almalki; Ali Obyan Alzahrani; Zain Osama Khayyat; Nouf Wasel Aljohani; Bashayr Nasyan Alotaibi; Abdullah Hamed Alzahrani; Wael Zaki Mahmoud Khan; Dhaifallah Abdulaziz Alzahrani; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Because medication errors often lead to adverse drug events (ADEs) longer hospital stays and increased medical costs they pose a serious risk to patient safety. Pharmacists and pharmacy technicians are both essential in avoiding these errors in clinical settings. Pharmacists are usually in charge of medication management and patient counseling while pharmacy technicians help with administrative inventory and dispensing tasks. Recent studies indicate that a team-based approach that entails pharmacy technicians and pharmacists working together to enhance medication safety and patient outcomes is advantageous. Methods: The literature on the collaboration between pharmacists and pharmacy technicians to reduce medication errors in clinical settings is examined in this review. The Cochrane Library PubMed and Scopus three of the biggest healthcare databases were thoroughly searched in order to locate studies that evaluate team-based interventions involving pharmacists and pharmacy technicians. Research was taken into consideration if it provided quantitative or qualitative data regarding the impact of these interventions on patient safety medication errors or healthcare efficacy. Results: Research from the literature shows that a team-based approach involving pharmacists and pharmacy technicians significantly reduces medication errors. In order to free up pharmacists to focus more on clinical responsibilities like medication reconciliation therapeutic monitoring and patient counseling pharmacy technicians assist by gathering medication histories maintaining inventory and ensuring proper dispensing. Pharmacy technicians involvement in tasks like medication reconciliation can reduce discrepancies by as much as 50% and team-based interventions have been linked in some contexts to a 60% decrease in medication errors. It has also been shown that adding pharmacy technicians to clinical teams boosts output and frees up pharmacists time to directly care for patients. Conclusion in clinical settings pharmacists and pharmacy technicians collaborate to enhance medication safety and patient support. There are fewer medication errors better patient outcomes and more effective healthcare because each professional can use their special skills in this model. However a clear role definition adequate training and supportive policies are required in order to successfully standardize pharmacy technician duties across healthcare settings. In addition to expanding these roles future research should concentrate on the long-term impacts of team-based pharmacy models on patient safety and healthcare costs.